Landownership and the gender gap in agriculture: Insights from northern Ghana. (December 2020) - Yokying, Phanwin; Lambrecht, Isabel
Highlights: We study the association of landownership with agency and achievements. Landownership is positively associated with women and men's agency in agriculture. Yet, gender gaps in agency persist among those who own land. Landownership alone may not suffice to reduce the gender gaps in agriculture. Abstract: Land provides the basis for food production and is an indispensable input for economic livelihoods in rural areas. Landownership is strongly associated with social and economic power. This holds not only across communities and households, but also within households. The link between landownership and women's empowerment has been relatively well documented in general, but not specifically in relation to agriculture. This paper aims to fill this gap by analyzing how self-reported primary ownership of land is associated with agency and achievements in agriculture among female and male farmers in northern Ghana. We use a recursive bivariate probit model on indicators in four domains: decisions on agricultural cultivation, decisions on farm income, agricultural association membership, and time allocation. Our empirical estimates indicate that primary landownership is positively correlated with decisions on agricultural cultivation. Yet, we also find that the gender gaps in participation in cultivation decisions and the use of agricultural earnings continue to persist among male and female primary landowners. Our findings underscore the importance of land in enhancing women's agency, but also point out that policies aiming to encourage women to become primary landowners (solely or jointly with their spouses) may not suffice to reduce gender inequality in agriculture.